Serendipity in Library Retrieval: Reinforcing Discovery through Visualization of Bibliographic Relationships - Dutta, Anirban; Mukhopadhyay, Parthasarathi (Journal of Information and Knowledge, 2021)
This work starts with a background study of serendipity, its meaning in the context of information discovery, its interrelation with bibliographic relationships, and the technical possibilities for practical implementation of a relationships based visual navigation in a library discovery interface to achieve serendipitous resource discovery. The methodology for developing the prototype consists of two components – theoretical base and practical steps. The theoretical framework includes an indepth study of the concept of bibliographic relationships as proposed by experts, as reflected in bibliographic data models and as included in bibliographic formats and metadata schemas. The practical sides deal with the application of the theoretical framework in designing a prototype that, in addition to other typical retrieval features, supports visual navigational facility driven by bibliographic relationships. The components, tools and standards of the entire software architecture are all open source and open standards.